Mithracinae (Decapoda: Brachyura) from the Brazilian coast: review of the geographical distribution and comments on the biogeography of the group - Alves,Douglas Fernandes Rodrigues (2012)
The geographical distribution of marine organisms, as a result of complex natural processes through geological time, has been changed, sometimes drastically, by species introductions. Instances of species introduction have been recorded worldwide, and the Brazilian coast is no exception. The present review provides an update of the geographical distribution of members of the brachyuran subfamily Mithracinae along the Brazilian coast. Of the 30 species of this subfamily recorded from Brazilian waters, the known geographical limits of more than 17 have been extended in recent decades. The records compiled here demonstrate the great importance of the Amazon River outflow on the geographical distribution of members of Mithracinae, acting as a biogeographical barrier for some species.